Prevalence and antimicrobial resistance in enterococci isolated from semi-intensive and free-range poultry farms in peri-urban Wakiso and rural Soroti, Uganda - Ochieng, Linnet; Ayebare, Dreck; Ndoboli, Dickson; Mbatidde, Irene; Tenhagen, B.-A.; Roesel, Kristina; Wampande, E.; Moodley, Arshnee (Elsevier, 2025)
Enterococcus spp. are commensal bacteria with increasing clinical relevance due to their role in antimicrobial resistance (AMR). This was a cross-sectional study conducted on broiler chickens in the Soroti and Wakiso districts. It assessed the prevalence, species distribution, AMR profiles, and the presence of mutations in the gyrA gene in antibiotic-resistant enterococci spp. A total of 402 environmental samples were collected, and 75% (303/402) tested positive for Enterococcus spp. The most frequently isolated species were E. faecalis (33.1%), followed by E. faecium (21.4%) and E. lactis (13.4%). Phenotypic resistance was observed to sulfamethoxazole-trimethoprim (21.2%), fluoroquinolone (11.9%), tigecycline (11.8%), ampicillin (4.1%), glycopeptides (2.3%), gentamicin (2.0%), and linezolid (1.0%). Resistance to fluoroquinolones, tigecycline, and sulfamethoxazole-trimethoprim was significantly associated with the semi-intensive system (Fisher’s exact p < 0.001). Only 3.3% of the isolates were multidrug-resistant. Eleven acquired resistance genes were detected, with tetL and tetM showing significant distribution differences between systems. Mutations in gyrA associated with fluoroquinolone resistance were also identified. While overall AMR levels were low, the detection of resistance to critically important antibiotics not approved for use in poultry highlights potential public health risks. These findings underscore the importance of routine AMR surveillance in poultry. It also highlights the need for deeper investigation into its role in AMR transmission and strategic interventions to limit the development of resistance in food animal production.